Microstructure and mechanical properties of ASTM A131 EH36 steel fabricated by laser aided additive manufacturing - Wang, Jingjing (2022)
In this paper, a direct laser deposition (DLD) process was used to print ASTM A131 EH36 high strength low alloy steel samples in four different orientations, namely, horizontal 0° (XY_0°) & 45° (XY_45°) and vertical 90° (XZ_90°) & 45° (XZ_45°), with an EH36 steel powder. The microstructures, mechanical properties and fracture behavior of the printed materials, were evaluated in detail. Tensile, charpy impact and fatigue tests were conducted to measure the mechanical properties of the materials. The results showed that all the EH36 steel samples printed in the four orientations satisfied the ASTM standards for the tensile and charpy impact properties of EH36 steel. The microstructures of the EH36 steel samples and the thermal cycles encountered in the different build orientations could be tuned by controlling the printing process parameters and scanning method. The microstructure was closely correlated with the mechanical properties of the built samples. The fatigue fracture mechanism of the printed EH36 steel samples was also proposed.